Does financial sector development promote economic globalization in Africa? - Samuel Tawiah Baidoo; Daniel Sakyi; Emmanuel Buabeng (Review of Economics and Political Science (REPS), 2025)
Purpose - This paper investigates whether financial sector development promotes economic globalization (EG) using data from 45 African countries. Design/methodology/approach - Using panel data of the selected African countries, the two-step system generalized method of moments estimation technique which is capable of solving any possible endogeneity problem is employed for the empirical analysis. Findings - The main finding is that all measures of financial sector development have a significant positive impact on EG in Africa. The results suggest that improving the financial sector development in a holistic manner is key in fostering EG in Africa. Originality/value - This present paper uses broader measures of EG and financial sector development. Using broader measures of these variables widens the policy scope in terms of policy adoption and implementation.
Keywords: 330; Africa; Economic globalization; Financial globalization; Financial sector development; Trade globalization